1996
DOI: 10.4319/lo.1996.41.8.1767
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of zooplankton grazing in an oligo‐mesotrophic lake using phytoplanktonic pigments as organic markers

Abstract: The impact of grazing by various zooplankton fractions (calanoid copepods, cyclopoid copepods, cladocerans, and small‐sized zooplankton: 80–315 µm) on various phytoplankton groups was measured in Lake Pavin (Central Massif, France) by means of phytoplankton pigments separated by HPLC as natural organic markers. The impact of grazing was determined from April to November in the depth‐sampling layers (0–7 and 7–20 m) in which most zooplankton organisms were concentrated. Selective grazing by consumers created sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 42 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Chl a samples were stored in a freezer. Phytoplankton pigments were analysed within one month after sampling to minimize the loss of pigments (Wright et al, 1991;Quiblier-Llobéras et al, 1996).…”
Section: Phytoplankton Samplingmentioning
confidence: 99%
“…Chl a samples were stored in a freezer. Phytoplankton pigments were analysed within one month after sampling to minimize the loss of pigments (Wright et al, 1991;Quiblier-Llobéras et al, 1996).…”
Section: Phytoplankton Samplingmentioning
confidence: 99%
“…Pigments were extracted and analyzed using an ion-pairing reagent solution (0.75 g tetrabutyl ammonium acetate and 7.7 g ammonium acetate in 100 mL of Easy-Pure water; Quiblier-Lloberas et al 1996). Briefly, all samples were ground in 5 mL of 90% high-performance liquid chromatography (HPLC)-grade acetone and transferred into scintillation vials (5 mL).…”
Section: Pigment Analysismentioning
confidence: 99%
“…Zooplankton samples intended for pigment analyses were anaesthetized in carbonated water to prevent regurgitation (Quiblier-Lloberas et al 1996), immediately put in the dark onto dry ice to limit organic matter degradation, and kept at cryogenic temperature (-80 8C) in the lab. Samples intended for isotope analyses were maintained in lake-filtered water overnight for gut clearance.…”
Section: Plankton Sampling and Sample Processingmentioning
confidence: 99%
“…As mentioned previously, canthaxanthin has been widely detected also in herbivores. Moreover, when Quiblier-Llobéras et al (1996) observed the summer planktonic community in an oligo-mesotrophic lake, canthaxanthin was found only in zooplankton, but it Table 2 Spearman rank order correlations for selected characteristics of pore-water dissolved organic matter (pDOM) and fossil pigments obtained by different methods (given in parentheses) for the analysed sediments of Lake Peipsi Pair of characteristics Spearman P-level was totally absent from phytoplankton. In the case of Lake Peipsi, further investigations should be conducted to determine whether canthaxantin is a marker pigment of specific cyanobacteria taxa or whether it is confined to herbivores.…”
Section: Onset and Course Of Eutrophicationmentioning
confidence: 99%